Epidemiological and Economic Burden of Pneumococcal Disease in Canadian Children - Geneviève Petit; Philippe De Wals; Barbara Law; Theresa Tam; Lonny James Erickson; Maryse Guay; Alicia Framarin (Canadian Journal of Infectious Diseases)
BACKGROUND: With the arrival of a new conjugate pneumococcal vaccine, it is important to estimate the burden of pneumococcal diseases in Canadian children. The epidemiological data and the economic cost of these diseases are crucial elements in evaluating the relevance of a vaccination program.